Glory, glory - Miller, Linda Lael.; Cassidy, Carla; Miller, Linda Lael. (Don Mills, Ont. : Harlequin, 2013)
"Glory, Glory": For Glory Parsons, "home for the holidays" wasn't exactly the stuff of sing-a-longs and sleigh rides. In fact, she dreaded it. Dreaded having to face the things she'd lost--her brother, a casualty of war; and Jesse Bainbridge, a casualty of her own weakness. She'd never been able to tell Jesse the reason she'd left him abruptly ten years ago, after she'd promised to love him forever
"Snowbound with the bodyguard": She'd been stranded by a snowstorm with nowhere to turn. But when all seemed lost, mom-on-the-run Janette Black saw the sign for Wild West Protective Services--and found Dalton West.
Glory, glory / Linda Lael Miller -- Snowbound with the bodyguard / Carla Cassidy.
Keywords: Man-woman relationships -- Fiction; Unmarried mothers -- Fiction; Birthfathers -- Fiction; Oregon -- Fiction; Romantic suspense fiction; Love stories